Pengaruh Pengetahuan Perpajakan, Modernisasi Sistem dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Laksmi P, Kadek Wulandari; Lestara Permana, Gusi Putu; Putri, Putu Wahyu Cahyani (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
The research was carried out with the aim of determining the influence of tax knowledge, modernization of the tax administration system, tax socialization on individual taxpayer compliance. The population uses individual taxpayers who have independent work/business. The sample in this study was 112 individual taxpayers. Multiple Linear Regression Analysis is used as a data analysis technique. The research results show that tax knowledge, modernization of the tax administration system and tax socialization have an influence on individual taxpayer compliance. Therefore, KPP Pratama East Denpasar is expected to be able to increase taxpayer compliance by increasing taxpayer knowledge, modernizing the tax administration system and routinely conducting tax outreach